STRUCTURAL DESIGN OF THE ECO-RESORT PROJECT ON THE LEMO-LEMO COAST, BULUKUMBA, SOUTH SULAWESI - Khoirul Basith, Milzam
Tourism in the Lemo-Lemo Beach area is a mainstay sector in supporting regional development. However, in recent years, there has been a decline in visitors caused by visitor boredom and sustainability issues. The eco-resort area on the Lemo-Lemo Coast covers an area of 1.7 hectares and is the solution to this problem. Various building facilities support the main and supporting functions of this infrastructure. The design of the upper structure consists of four buildings: Service and Accomodation, Swimming Pool, Multipurpose Room, and A unit. The Special Moment Resisting Frame System is applied to reinforced concrete structures, while the wooden structures use a Wooden Frame System. The modeling of infrastructure model uses the ETABS 18 program. The detailing of reinforcement of reinforced concrete elements used the spColumn program for columns and SAFE 2016 for plates. The result of this final project is an earthquake-resistant structural design with reinforcements and connections that comply with SNI regulations.